Critical success factors in e-learning – a case study - Asliaty Atim,; Ilidina Mahadi,; Nurul Emilia Diyana Abdul Malik,; Kiziltas, Ercan (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the development of the Internet and Information, Communication Technology (ICT), many educational institutions offer a blended education in which students learn via electronic and online media as well as traditional face-to-face teaching. However, the Covid-19 pandemic has made online education or e-learning compulsory in almost all educational institutions globally. This research has been designed to indicate the critical success factors (CSF) for e-learning. This case study focused on an in-depth probing from students’ perspectives on the factors that affect the success of the course in a semester. It involved an IT course for undergraduates involving a 14-week learning about the theory and practical aspects of basic ICT skills. The researchers collected the data using a mixed-method approach via self-constructed questionnaire and semi-structured interview evaluating the students’ perspectives on their learning preference, participation and understanding in the course and the instructor’s technological skills, pedagogical strategies and subject competency in conducting the course. In the findings, the students have shown high agreement in persisting to learn despite Internet interruption or problems. The students have also agreed that they interacted with other students after class time and were able to use their prior knowledge and applied the knowledge learnt from the course to other courses. Other findings included good pedagogical and technological skills demonstrated by the lecturer. The study has contributed to the theoretical aspect of Instructional Design for online learning which anticipates CSF.